2007
DOI: 10.3748/wjg.v13.i9.1445
|View full text |Cite
|
Sign up to set email alerts
|

KN-93, a specific inhibitor of CaMKII inhibits human hepatic stellate cell proliferation бin vitro��

Abstract: AIM:To investigate the effects of KN-93, a CaMKⅡ selective inhibitor on cell proliferation and the expression of p53 or p21 protein in human hepatic stellate cells. METHODS:Human hepatic stellate cells (LX-2) were incubated with various concentrations (0-50 mmol/L) of KN-93 or its inactive derivative, KN-92. Cell proliferation was measured by CCK-8 assay, and the expression of two cell cycle regulators, p53 and p21, was determined by SDS-PAGE and Western blotting.RESULTS: K N -9 3 ( 5 -5 0 mm o l / L ) d e c r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 20 publications
2
11
0
2
Order By: Relevance
“…9A). These data are also in agreement with previously published data [21]. In addition, KN-93 upregulated the number of cells in G2/M phase from 25.5% (control) or 25.6% (KN-92) to 34.0% (KN-93), analogous to the findings noted in Fig.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…9A). These data are also in agreement with previously published data [21]. In addition, KN-93 upregulated the number of cells in G2/M phase from 25.5% (control) or 25.6% (KN-92) to 34.0% (KN-93), analogous to the findings noted in Fig.…”
Section: Resultssupporting
confidence: 93%
“…Patel and colleagues demonstrated that Ca 2+ and calmodulin (CaM) regulate phosphorylation of Cdc25C in HeLa cells; the mechanism depended on CaM kinase II [28]. Here we confirm that the CaMK II inhibitor KN-93 blocked LX-2 proliferation, as noted in a recent study [21], and we now provide evidence that this compound also blocks G2/M progression and Cdc25C phosphorylation. Finally, growth arrest of HSC at the G2/mitosis interface has been demonstrated previously [29], suggesting that this may be a critical checkpoint in the HSC cell cycle and thus a valid potential target for anti-fibrotic drug therapy.…”
Section: Discussionsupporting
confidence: 90%
“…In various cell types, inhibition of CaMKII has been shown to inhibit proliferation [65][66][67]. Indeed, in vascular smooth muscle cells in culture, proliferation and migration can be induced by serum withdrawal and this results in the specific induction of the q2 splice variant of CaMKII, despite the fact that these cells already express another isoform of CaMKIIq.…”
Section: Splice Isoformsmentioning
confidence: 97%
“…concentration in response to PDGF has been definitely confirmed [32]. Also, our previous study showed that KN-93 significantly inhibited HSC proliferation [25]. Accordingly, we deduced that CaMKII might be an important regulator mediating PDGF pathway in human HSC.…”
Section: Discussionmentioning
confidence: 65%
“…signal transduction and regulates numerous cellular processes, including cell proliferation, apoptosis, gene expression, and neurotransmission [19][20][21][22][23][24]. Our earlier study first reported that the interruption of CaMKII by its specific inhibitor, KN-93, reduced human HSC proliferation [25]. We have also found that KN-93 increased the expression of P53 and P21, which are important suppressor proteins controlling cell cycle progression.…”
Section: Introductionmentioning
confidence: 94%